2019
DOI: 10.3390/nu11112829
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antibacterial and Antiinflammatory Activities of Proanthocyanidins from Pelargonium sidoides DC Root Extract

Abstract: The study explores antibacterial, antiinflammatory and cytoprotective capacity of Pelargonium sidoides DC root extract (PSRE) and proanthocyanidin fraction from PSRE (PACN) under conditions characteristic for periodontal disease. Following previous finding that PACN exerts stronger suppression of Porphyromonas gingivalis compared to the effect on commensal Streptococcus salivarius, the current work continues antibacterial investigation on Staphylococcus aureus, Staphylococcus epidermidis, Aggregatibacter actin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 59 publications
3
33
0
2
Order By: Relevance
“…Genetic susceptibility is believed to be due to changes in the subject’s genes that lead to i) a lower efficiency of the immune system in controlling the growth of pathogenic bacteria; and/or ii) an imperfect regulation of the inflammatory response [ 28 , 29 , 30 , 31 , 32 ] which leads to an increase in the destructive side effects of inflammation [ 33 , 34 , 35 , 36 ]. As a matter of fact, Jekabsone et al [ 37 ] explored antibacterial, antinflammatory and cytoprotective capacity of Pelargonium sidoides DC root extract (PSRE) and proanthocyanidin fraction from PSRE (PACN) under conditions characteristic for periodontal disease. They found that PSRE and especially PACN possess strong antibacterial, anti-inflammatory and gingival tissue protecting properties under periodontitis-mimicking conditions and are suggestable candidates for the treatment of periodontal disease.…”
Section: Editorialmentioning
confidence: 99%
“…Genetic susceptibility is believed to be due to changes in the subject’s genes that lead to i) a lower efficiency of the immune system in controlling the growth of pathogenic bacteria; and/or ii) an imperfect regulation of the inflammatory response [ 28 , 29 , 30 , 31 , 32 ] which leads to an increase in the destructive side effects of inflammation [ 33 , 34 , 35 , 36 ]. As a matter of fact, Jekabsone et al [ 37 ] explored antibacterial, antinflammatory and cytoprotective capacity of Pelargonium sidoides DC root extract (PSRE) and proanthocyanidin fraction from PSRE (PACN) under conditions characteristic for periodontal disease. They found that PSRE and especially PACN possess strong antibacterial, anti-inflammatory and gingival tissue protecting properties under periodontitis-mimicking conditions and are suggestable candidates for the treatment of periodontal disease.…”
Section: Editorialmentioning
confidence: 99%
“…After cytocompatibility and antibacterial assays, the following optimal (intended as safe for cells and effective toward bacteria) AMPs concentrations were selected and used in further experiments: Nisin 75 µg/ml and LL-37 10 µg/ml. To verify the antibacterial activity of the targeted AMPs a cells-bacteria coculture assay was performed as in our previous studies (Jekabsone et al, 2019;Cochis et al, 2020). The co-culture method was designed to monitor the viability of both cells and bacteria that are challenging in the same environment for the same surface colonization, thus allowing for the validation of the AMPs' targeted activity toward bacteria (Cochis et al, 2020).…”
Section: Co-culturesmentioning
confidence: 99%
“…After the evaluation of AMPs cytocompatibility and antibacterial activity, the following concentrations were selected as the most promising in reducing the pathogen metabolism while preserving the cell viability that was considered as the key factor in this study: 75 µg/ml Nisin and 10 µg/ml LL-37. However, those results were obtained by keeping separated cells and bacteria in different environments; so, to check whether the AMPs activity was really targeting only (or at least mainly) bacteria, a co-culture assay was performed as we have previously described (Jekabsone et al, 2019;Cochis et al, 2020) to evaluate the AMPs performance in the same environment containing both cells and bacteria. Therefore, it should be clarified that only the number of adherent bacteria was evaluated as suggestive for those able to colonize the same surface as cells when cultivated in the same environment.…”
Section: Co-culturesmentioning
confidence: 99%
“…Moreover, these plants do not include ibuprofenlike substances in their composition, but pharmacologically different bioactive molecules (e.g., coumarins, polyphenols, and triterpenes), which do not act as enhancers of ACE2 receptor expression. 3,4 In addition, active components of medicinal plants have always been considered an important source of clinical therapeutics, with a multitarget pharmacologic activity ascribed to their great chemical diversity. 5…”
Section: First Considerationmentioning
confidence: 99%
“…appear eligible for further studies to find effective remedies against SARS-CoV-2 infection, as they have an interesting combination of antimicrobial and anti-inflammatory properties, thus being capable of improving the patient's phlogistic symptoms and potentially inhibiting the viral replication at the same time. 4,8 The usefulness of such plants has also been underscored by systematic reviews investigating their clinical efficacy and safety. 8,9 Therefore, based on scientific evidence and empirical tradition, it is possible to hypothesize a potential role of some plants during the evolution of the disease from prevention to rehabilitation, 10 with some consequent recommendations (Table 1).…”
Section: Fourth Considerationmentioning
confidence: 99%